Evolutionary Characteristics of Project Interdependent Network within National Quality Award Projects of China - Fu Lixin; Liu Liang (E3S Web of Conferences, 2021)
The research on the evolutionary law of project interdependent network is the innovation in construction industry. Based on the complex network theory and method, this research establishes the projectproject correlation network, and it is built based on the actual case of the National Quality Award Projects of China (NQAPC). We aim to systematically analyze the structural characteristics and evolution mechanism of the project interdependent network by using global network parameters. As network size increases, the degree follows power-law distribution, the average path length tends to decrease, and the clustering coefficient and heterogeneity gradually increases. The research results may help managers achieve higher performance in strategic network management of construction projects.